A Double-Antibody Sandwich ELISA for Sensitive and Specific Detection of Swine Fibrinogen-Like Protein 1 - Zhang, Xin; Zhu, Haipeng; Zheng, Xu; Jiao, Yunjie; Ning, Lulu; Zhou, En-Min; Mu, Yang (Frontiers in Immunology, 2021)
Fibrinogen-like protein 1 (FGL1), a member of the fibrinogen family, is a specific hepatocyte mitogen. Recently, it has been reported that FGL1 is the main inhibitory ligand of lymphocyte activating gene 3 (LAG3). Furthermore, the FGL1-LAG3 pathway has a synergistic effect with programmed death 1 (PD-1)/programmed death ligand 1 (PD-L1) pathway and is regarded as a promising immunotherapeutic target. However, swine FGL1 (sFGL1) has not been characterized and its detection method is lacking. In the study, the sFGL1 gene was amplified from the liver tissue of swine and then inserted into a prokaryotic expression vector, pQE-30. The recombinant plasmid pQE30-sFGL1 was transformed into competent JM-109 cells. The recombinant sFGL1 was induced expression by isopropyl-β-d-thiogalactoside (IPTG) and the purified sFGL1 was used as an antigen to produce mouse monoclonal antibody (mAb) and rabbit polyclonal antibody (pAb). After identification, a double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) for sensitive and specific detection of sFGL1 was developed. Swine FGL1 in samples was captured by anti‐sFGL1 mAb followed by detection with anti‐sFGL1 rabbit pAb and HRP-conjugated goat anti-rabbit IgG. The limit of detection of the developed sFLG1-DAS-ELISA is 35 pg/mL with recombinant sFLG1. Besides, it does not show cross‐reactivity with the control protein. Then serum samples of PRRSV-negative and -positive pigs were tested with the established DAS-ELISA and calculated according to the equation of y=0.0735x+0.0737. The results showed that PRRSV infection enhanced the serum FGL1 levels significantly. Our research provides a platform for the research on the functional roles of FGL1.